2021
DOI: 10.1177/03795721211008021
|View full text |Cite
|
Sign up to set email alerts
|

School Canteens in Selected Areas in Indonesia: A Situation Analysis

Abstract: Background: The school canteen has a massive impact on the dietary intake and nutritional status of school-age children and adolescents. This study aimed at assessing the current situation of school canteens in selected areas in Indonesia and relevant knowledge, attitudes, and behaviors of school-going children and adolescents. Methods: A qualitative study was implemented in a purposive sample of 18 schools in Klaten and West Lombok districts with 2 comparison schools in Jakarta and Klaten. Focus group discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…These findings also match those observed in previous studies that reported inconsistent implementation of canteen policies in Victoria and low adherence to canteen policy (Lawlis et al, 2016) with many discretionary food items and lack of healthy food items on the canteen menus (Woods et al, 2014). International studies previously reported similar criticism of school canteens and highlighted inequity across schools (Rachmadewi et al, 2021;Porto et al, 2015;Fitzpatrick et al, 2017). For example, Indonesian and Brazilian school canteens have heavily promoted non-nutritious snacks to children (Porto et al, 2015;Rachmadewi et al, 2021).…”
Section: Improving Fne In Primary Schoolssupporting
confidence: 88%
See 3 more Smart Citations
“…These findings also match those observed in previous studies that reported inconsistent implementation of canteen policies in Victoria and low adherence to canteen policy (Lawlis et al, 2016) with many discretionary food items and lack of healthy food items on the canteen menus (Woods et al, 2014). International studies previously reported similar criticism of school canteens and highlighted inequity across schools (Rachmadewi et al, 2021;Porto et al, 2015;Fitzpatrick et al, 2017). For example, Indonesian and Brazilian school canteens have heavily promoted non-nutritious snacks to children (Porto et al, 2015;Rachmadewi et al, 2021).…”
Section: Improving Fne In Primary Schoolssupporting
confidence: 88%
“…, 2014). International studies previously reported similar criticism of school canteens and highlighted inequity across schools (Rachmadewi et al. , 2021; Porto et al.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Frequently, street foods may lack freshness and contain excessive additives. Alarming data reveal that around half of the street food available near schools contains harmful chemicals like sodium cyclamate and saccharin as artificial sweeteners, as well as sodium benzoate as a preservative (Hadi et al, 2022; Rachmadewi et al, 2021). To make matters worse, street food is often contaminated with pollutants, sewage, unclean water, and even cigarette smoke (Cempaka et al, 2019; Damastuti et al, 2021; Dyna et al, 2018; Rosida & Windraswara, 2017).…”
Section: Introductionmentioning
confidence: 99%